Unusual presentation of phaeochromocytoma - Hope, D C D (BMJ Case Rep, 2016)
A 44-year-old woman, with a background of heart, lung and renal transplantation secondary to cystic fibrosis and type 1 diabetes, presented with tachycardia, hyperglycaemia, nausea and vomiting. She was initially managed for diabetic ketoacidosis with severe dehydration. However, persistent episodic hypertension and tachycardia led the investigating team to identify significantly raised urinary metanephrines and a left-sided adrenal mass; Iodine-123-meta-iodobenzylguanidine single photon emission computer tomography scan (MIBG SPECT/CT) showed avid uptake of tracer, confirming a left-sided phaeochromocytoma. She was started on medical management and is awaiting an elective laparoscopic procedure. This case describes the presentation of a unilateral phaeochromocytoma as ketoacidosis in a patient with type 1 diabetes with no other apparent precipitant. This highlights the metabolic counter-regulatory effect of excess catecholamines in addition to the inotropic/chronotropic effects that are associated with this adrenal tumour. Recognition of atypical signs and symptoms may point towards an atypical precipitant of diabetic ketoacidosis—a medical emergency presenting to front-line clinicians.